Sensitivity of Bacilloscopy, Culture and ELISA Methods to Diagnose Lung Tuberculosis, in Patients From Vargas State-Venezuela - J Betancourt; N Ruiz; P Cruces; W Velásquez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2002)
This research was conducted with the objective of evaluating sensitivity in diagnosing lung tuberculosis, through bacilloscopy, culture and ELISA methods in respiratory symptomatic patients who attended the Neumonology  consultation Department from Sanitary District N° 6, La Guaira, Vargas State-Venezuela. To achieve this, two extended sputum samples were carried  out, which were stained by the Ziehl-Neelsen method (Bacilloscopy). Each sample was sown using the method proposed by Ogawa- Kudoh. A blood sample was taken from the patients with positive sputum samples by bacilloscopy and culture methods to detect antibodies for M. tuberculosis. Out of the 200 samples analyzed to diagnose lung tuberculosis, 20 (10,0%) proved positive through the culture method, and only 11 (5,5%) were serum-positive by the ELISA method. The culture, bacilloscopy, and ELISA methods showed a sensitivity of 100, 65 and 55 % respectively. These results suggest that the Ogawa-Kudoh culture method is much more sensitive; therefore, this method gives more reliable and accurate results, especially in samples with low bacillus density.